2012
DOI: 10.3928/00485713-20120705-07
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Obsessive-Compulsive Disorder in Pregnancy

Abstract: It's more than a new destination. It's a more powerful platform. Personalized to place your interests fi rst. Subspecialized to fi t your daily practice. At Healio.com, you'll fi nd more new ways to stay informed, gain perspective, and earn CME credits-with more exciting updates arriving all the time. • Award-winning news reporting • Dynamic video and multimedia • Curbside Consultation: Q&A • CME and other educational activities • Peer-reviewed journals • Blogs Powered by SLACK Incorporated® 12-0672_PSYCH Get … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the only existing randomized controlled trial in this population, Timpano and colleagues ( 2011 ) found that a cognitive-behavioral prevention program for pregnant women at risk for OCD resulted in signifi cant reductions in obsessions and compulsions during the fi rst 6 months postpartum. Case studies have also demonstrated successful treatment of perinatal OCD with CBT, either as a stand-alone treatment (Christian and Storch 2009 ) or with adjunctive pharmacotherapy (Flosnik and Khin 2012 ).…”
Section: Psychotherapymentioning
confidence: 99%
“…In the only existing randomized controlled trial in this population, Timpano and colleagues ( 2011 ) found that a cognitive-behavioral prevention program for pregnant women at risk for OCD resulted in signifi cant reductions in obsessions and compulsions during the fi rst 6 months postpartum. Case studies have also demonstrated successful treatment of perinatal OCD with CBT, either as a stand-alone treatment (Christian and Storch 2009 ) or with adjunctive pharmacotherapy (Flosnik and Khin 2012 ).…”
Section: Psychotherapymentioning
confidence: 99%
“…Patient's preference: CBT is preferred by patients with no co-morbid conditions, mild to moderate OC symptoms, or those with a preference for psychotherapy over medications [110]. Furthermore, CBT is the preferred choice for pregnant women [110].…”
mentioning
confidence: 99%
“…Furthermore, CBT is the preferred choice for pregnant women [110]. CBT is highly effective for patients who did not or partially respond to treatment with psychotropic medications [111,112].…”
mentioning
confidence: 99%